Intestinal microbiota are involved in the immunomodulatory activities of longan polysaccharide. Issue 11 (15th August 2017) - Zhang, Jiachao; Yang, Guangmei; Wen, Yazhou; Liu, Sixin; Li, Congfa; Yang, Ruili; Li, Wu
Abstract: It is difficult for polysaccharides to be directly absorbed through the intestine, which implies other utilization mechanisms involved in the bioactivity performance of polysaccharide. In this study, the multi‐omics approach was applied to investigate the impacts of longan polysaccharide on mouse intestinal microbiome and the interaction between the polysaccharide‐derived microbiome and host immune system. According to the result, the longan polysaccharide showed a significant improvement in the typical intestinal immunity index of mice. Meanwhile, at the taxonomy level, the intestinal microbiota from the control group and polysaccharide group were highly distinct in organismal structure. At the functional level, a significant decline in the microbial metabolites of pyruvate, butanoate fructose and mannose in the control group was found. Additionally, a significant increase was observed in the succinic acid and the short‐chain fatty acid, including acetic acid, propionic acid and butyric acid, in the polysaccharide group. Furthermore, the multi‐omic based network analysis indicated that the intake of longan polysaccharide resulted in the changes of the intestinal microbiota as well as the gut metabolites, which led to the enhancement of host's immune function under the stress conditions. These results indicated the polysaccharide‐derived changes in intestinal microbiota were involved in the immunomodulatory activities. Abstract : The results of this study indicate that the polysaccharide‐derived changes in the intestinal microbiota and the gut metabolites were involved in the bioactivity performance of polysaccharide. This may be one of the important mechanisms of polysaccharide regulation of immune immunity. There may be the need to re‐examine the immunoregulatory activity of polysaccharides in vitro .